The Enteropathogenic E. coli (EPEC) Tir Effector Inhibits NF-κB Activity by Targeting TNFα Receptor-Associated Factors - Ruchaud-Sparagano, Marie-Hélène (Public Library of Science, 2011)
Enteropathogenic Escherichia coli (EPEC) disease depends on the transfer of effector proteins into epithelia lining the human small intestine. EPEC E2348/69 has at least 20 effector genes of which six are located with the effector-delivery system genes on the Locus of Enterocyte Effacement (LEE) Pathogenicity Island. Our previous work implied that non-LEE-encoded (Nle) effectors possess functions that inhibit epithelial anti-microbial and inflammation-inducing responses by blocking NF-κB transcription factor activity. Indeed, screens by us and others have identified novel inhibitory mechanisms for NleC and NleH, with key co-operative functions for NleB1 and NleE1. Here, we demonstrate that the LEE-encoded Translocated-intimin receptor (Tir) effector has a potent and specific ability to inhibit NF-κB activation. Indeed, biochemical, imaging and immunoprecipitation studies reveal a novel inhibitory mechanism whereby Tir interaction with cytoplasm-located TNFα receptor-associated factor (TRAF) adaptor proteins induces their proteasomal-independent degradation. Infection studies support this Tir-TRAF relationship but reveal that Tir, like NleC and NleH, has a non-essential contribution in EPEC's NF-κB inhibitory capacity linked to Tir's activity being suppressed by undefined EPEC factors. Infections in a disease-relevant intestinal model confirm key NF-κB inhibitory roles for the NleB1/NleE1 effectors, with other studies providing insights on host targets. The work not only reveals a second Intimin-independent property for Tir and a novel EPEC effector-mediated NF-κB inhibitory mechanism but also lends itself to speculations on the evolution of EPEC's capacity to inhibit NF-κB function.